IMPLEMENTASI KEBIJAKAN PENGENDALIAN BANJIR PROVINSI DKI JAKARTA MELALUI PROYEK KANAL BANJIR TIMUR - Zahranum Ramadhayanti; Turtiantoro .; Kushandajani . (Journal of Politic and Government Studies, 2015)
Development is a process of social change that is accompanied by or meaningful community participation in order to improve the standard of living of an unfavorable situation into a better one. Various development policies that have been made by the government as an effort to overcome the flood problem in the area of Jakarta has a lot to do, namely to build physical infrastructure such as roads, drainage, polders, as well as other supporting infrastructure. One of the government's efforts to control floods in the North-East region of Jakarta is by the efforts of the East Flood Canal project development / KBT, the concept has entered into the Master Plan (Master Plan) 1973. The Government through the Ministry of Infrastructure (now the Ministry of Public Works and Public Housing) and Jakarta Provincial Government are the institutes that are responsible for the implementation of the East Flood Canal project / KBT.The purpose of this study is to determine the implementation of flood control in the area of Jakarta through the East Flood Canal project / KBT, supporting factors and inhibiting factors in these implementations. The method of this study using a qualitative approach is descriptive-analytic. There are two variables in view of the implementation of flood control in the area of Jakarta through the East Flood Canal project / KBT, the contents of the policy and the policy context. Supporting factors of the implementation of flood control in the area of Jakarta are a clear policy, the commitment of implementing the policy, and the budget. While the inhibiting factors are the coordination of the implementation, supervision of government, land acquisition that is unresolved, people who do not have a sense of participation / awareness do not participate maintaining and caring for the existence of the East Flood Canal buildings / KBT.Implementation of Flood Control through the East Flood Canal project is considered as effective way for flood control in the area of Jakarta. However, there should be an improvement in surveillance and control channel region by the central government (Ministry of Public Works and Housing of the People) and local government (Jakarta). Thus, we need the cooperation of every institute private, and people to run in accordance with the development plan of the East Flood Canal project / KBT listed in the Regional Regulation (Perda) of Jakarta Number 06 of 1999 on Spatial Planning Year 2010 Jakarta.Keywords: Implementation, Flood Control, East Flood Canal / KBT